Pengenalan metode HOTS dalam upaya meningkatkan pola berpikir kritis problem solving - Sutiasih, Nur Maulia Sari (Maliki Interdisciplinary Journal, 2024)
The purpose of this article was to analyze the causes of low development of a critical pattern of thought in resolving a problem. The method used to improve a critical mind-set is with underlying problems. Higher order thinking skills (hots) is a process to increase the ability to think creatively, critical and able to resolve problems. Critical patterns of thought should be cultivated from an early age, where at the earliest age the child will be more curious and try to find the best solution in solving it. Developing this hots method, by giving the problem where students are encouraged to find the best possible problem for the problem. This method can be applied in elementary school/equal schools to berate children’s critical mind-set in finding the best addictive problem. The role of teachers and parents in the application of the hots method in the hots problem is crucial, where parents and teachers can help to monitor what is happening to the child, then is given understanding of the problem and given solutions, so that the child will be able to think of the best solutions to the problem under consideration of the advice of the parents and teacher.